Response of dental pulp capped with calcium-silicate based material, calcium hydroxide and adhesive resin in rabbit teeth - cynthia kassis (Universidade Estadual de Campinas, 2021)
Direct pulp capping induces a local inflammatory process. Several biomaterials have been used for this procedure. The aim of this study was to compare the dentinal bridge thickness using three different pulp capping biomaterials with the conventional technique (high speed diamond bur) or Er-Yag laser, 1 month after pulp effraction. Materials and Methods: Forty two Class V cavities were prepared on the buccal surface of 4 maxillary incisors and 2 mandibular incisors of New Zealand rabbits. Specimens were divided into 6 treatment groups. Teeth were treated with: In Group 1: Er-Yag laser and Biodentine® (Septodont), in Group 2: Er: Yag laser and calcium hydroxide (Dycal® Dentsply), in Group 3: Er: Yag laser and adhesive system (Prime& Bond® NT Dentsply), in Group 4: high speed diamond bur and Biodentine® (Septodont), in Group 5: high speed diamond bur and calcium hydroxide (Dycal® Dentsply), and in Group 6: high speed diamond bur and adhesive system (Prime& Bond® NT Dentsply). The preparation was done with copious irrigation. The animals were sacrificed at 30 days and the teeth were extracted and prepared for histological analysis. Results: In the group of « laser Er-Yag », iatrogenic pulpal wounds treated with Biodentine® were covered with a thick hard tissue barrier after 1 month. The difference was not significant with the groups of Dycal® used with Er: Yag laser and high speed diamond bur. Prime& Bond® NT Dentsply specimens showed a thin dentinal bridge layer. Conclusion: At 1 month, Er-Yag laser proved to be useful with Biodentine® for direct pulp capping procedures.